(3ENJUGQ GdLHQ hGdebGHdIs - (3eMeO Hf YeQ Hf eMeO, GHf HOQs
(3ChdgG (B:s
(3EYde Cf GdLHQ jOhQ Ydi KdGKI GTjGA hgj CehGd hYOO hLPhQg aGdLPQ efgG eG VQH ai eKdI ef GdhGMO heG Ohfg ef GdcShQ heG ahbg ef GdCYOGO s
(3BNQgG (B:s
(3hgPG GdYed ai gPg GdeSFdI ceG PcQfG cPdc Cf JLYd CMOgeG TjFkG jNQL eG eY GdKGfi ef BNQ GdTQWjf Ke jNQL ajeI GdTF ef Pdc aGage JUH Ef TGA Gddg Je cJGH GdLHQ hGdebGHdI HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3fSNI fajSIs
(3YdjgG bQGAI hJUMjM SfI (B764 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(936/1) s
Keywords: (3GdQjGVjGJs